Why did Australia go into East Timor? - Keti Ivanovska. (2008)
If East Timor was a pebble in the shoe of Indonesia, as former Indonesian Foreign Minister Ali Alatas once dubbed it, then it was a black soil on the conscience of Australia. Sine 1979, successive Australian governments had placed great emphasis upon building a strong relationship with the Indonesian regime.